Digitalisasi Administrasi Pajak UMKM Sektor Distributor di Kota Batam : Studi Kualitatif tentang Pengalaman, Tantangan, dan Strategi Adaptasi Pelaku Usaha di Era Kebijakan Pajak Terbaru - Erwin Sya'ban Ardi Wibowo; Anthony Salim; Ernest Kusuma Dharma; Limas Putra; Hansen Nicholas; Herodes Herodes (Pusat Riset dan Inovasi Nasional, 2026)
The digitalization of tax administration has become one of the Indonesian government's strategic initiatives to improve efficiency, transparency, and taxpayer compliance. However, the implementation of digital tax systems among Micro, Small, and Medium Enterprises (MSMEs), particularly distributor-sector MSMEs in Batam City, still faces various administrative and technical challenges. This study aims to examine the experiences, risk perceptions, and adaptation strategies of distributor MSME actors in responding to the digitalization of tax administration following the implementation of the Harmonization of Tax Regulations Law (UU HPP). The research employed a qualitative approach using a phenomenological method. Data were collected through in-depth interviews with seven distributor MSME owners in Batam City who had utilized digital tax systems such as e-Filing and Coretax. The findings indicate that most business actors still experience limitations in technical understanding, concerns regarding reporting errors, and difficulties adapting to changes in digital tax systems and regulations. To address these challenges, MSME actors developed several adaptation strategies, including the use of tax consultants, hybrid manual-digital bookkeeping systems, and informal assistance through the internet and business networks. This study highlights that the success of tax digitalization requires a more adaptive approach, stable systems, and policies that are aligned with the characteristics of local MSMEs.